PEMETAAN STATUS HARA P, pH dan C organik TANAH SAWAH DI DESA HILIBADALU KECAMATAN SOGAEADU KABUPATEN NIAS - Charlan B Lombu (Talenta Publisher, 2017)
The purpose of this research is to survey and mapping nutrient status of total phosphate, available phosphate, soil pH and organic carbon at paddy fields Hilibadalu Village Sogaeadu District Nias Regency and its influence on rice production. Soil samples were analyzed at the Analytical Laboratory of PT Socfindo Indonesia North Sumatera Province. Which began in October to December 2016. The method used is the Free Grid Survey semi-detailed level survey and analysis of nutrient data total phosphate by Acid destruction method (HClO4), available phosphate by Bray II method, soil pH by H2O extraction and organic carbon by Walkley & black method and then interpret to the map nutrient status. The result of research showing that status total phosphate classified by 3 statuses such as medium (81,59 ha), high (81,15 ha) and very high (27,26 ha). Available phosphate classified in 3 nutrient status such as very low (39,11 ha), low (137,40 ha) and medium (13,49 ha). Soil pH classified into 2 statuses such as moderately acidic (30,16 ha) and strongly acidic (159,84 ha). Organic carbon classified by 3 nutrient statuses such as very low (3,06 ha), low (135,84 ha) and medium (51,10 ha). Available phosphate and organic carbon affect rice production in Hilibadalu Village Sogaeadu District Nias Regency.